Current research trends on dry, near-dry and powder mixed electrical discharge machining - Rahman Khan, Md. Ashikur; Rahman, Md. Mustafizur; Mat Noor, Muhamad; Maleque, Md. Abdul (Trans Tech Publications, Switzerland, 2011)
Electrical discharge machining (EDM) technique has been widely used in modern metal working industry for producing complex cavities in dies and moulds, which are otherwise difficult to create by conventional machining. The process has the advantage of being able to machine hardened tool steels. However, its low machining efficiency and poor surface finish restricted its further applications. To address these problems, one relatively new technique used to improve the efficiency and surface finish is EDM in the presence of powder suspended in the dielectric fluid. Powder mixed electric discharge machining (PMEDM) is one of the recent innovations for the enhancement of capabilities of EDM process. In PMEDM, the electrically conductive powder is mixed in the dielectric fluid of EDM, which reduces the insulating strength of the dielectric fluid and increases the spark gap between the tool and workpiece. As a result, the process becomes more stable, thereby, improving the material removal rate (MRR) and surface finish. Moreover, the surface develops high resistance to corrosion and abrasion. This paper presents the current research trends on dry, near dry EDM and review on research carried out in the area of PMEDM.